Sporadic late-onset nemaline myopathy: a case report of a treatable cause of cardiac failure. Issue 1 (22nd December 2020) - Turnquist, Casmir; Grogono, Joanna C; Hofer, Monika; Pitcher, Alex
Abstract: Background : Sporadic late-onset nemaline myopathy (SLONM) is a rare, acquired, adult-onset myopathy, characterized by proximal muscle weakness and the pathognomonic feature of nemaline rods in muscle fibres. Sporadic late-onset nemaline myopathy is associated with cardiac pathology in case reports and small case series, but the severity of cardiac disease is generally mild and rarely requires specific treatment. This case report describes severe heart failure as an early feature of SLONM, which responded to specific treatments, and highlights SLONM as a potentially reversible cause of heart failure. Case summary : A 65-year-old woman presented with progressive muscle weakness and a dramatic loss of muscle bulk in her thighs, followed by progressive effort breathlessness over an 18-month period. She required a wheelchair to ambulate. A diagnosis of SLONM was made on histopathological assessment of a muscle biopsy along with electron microscopy. An echocardiogram showed a severely dilated and impaired left ventricle. She was treated with standard heart failure medications and autologous stem cell transplantation, which resulted in improvement of both her cardiac and muscle function, and allowed her to walk again and resume near-normal functional performance status. Discussion : Cardiomyopathy can be a relatively early and life-threatening feature of SLONM and even in severe cases can be effectively treated with standard heart failure medications and autologous stem cell transplantation.